(untitled) (Journal of Health, Population and Nutrition, 2011)
Five million children aged less than five years die annually due to diarrhoea. The aim of the study was to identify some possible contributing factors for persistent diarrhoea. Seven weaning foods, including a locally-made food, were evaluated by estimating the microbial load using the most probable number method and aflatoxin levels (AFM1, AFG1, AFG2, and AFB2) by immunoaffinity column extraction and high-performance liquid chromatography (HPLC) with detection of fluorescence. The results showed that the locally-made weaning food had the highest microbial count (2,000 cfu/g) and faecal streptococcal count (25 cfu/g). Moulds isolated were mainly Aspergillus niger, A. flavus, A. glaucus, Cladosporium sp., and Penicillium sp. The home-made weaning food recorded the highest fungal count (6,500 cfu/g). AFM1 of the weaning foods was 4.6-530 ng/mL. One weaning food had AFB1 level of 4,806 ng/g. Aflatoxin metabolites, apart from AFM1 and AFB1 present in the weaning foods, were AFG1 and AFG2. There were low microbial counts in commercial weaning foods but had high levels of aflatoxins (AFM1, AFG1, AFG2, AFB1, and AFB2). Growth and development of the infant is rapid, and it is, thus, possible that exposure to aflatoxins in weaning foods might have significant health effects. Key words: Aflatoxins; High-performance liquid chromatography; Microbial contamination; Microbial count; Weaning foods; Nigeria DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8459 JHPN 2011; 29(4): 415-419